Rapid screening for SARS-CoV-2 variants of concern in clinical and environmental samples using nested RT-PCR assays targeting key mutations of the spike protein. (1st June 2021) - La Rosa, G; Mancini, P.; Bonanno Ferraro, G.; Veneri, C.; Iaconelli, M.; Lucentini, L.; Bonadonna, L.; Brusaferro, S.; Brandtner, D.; Fasanella, A.; Pace, L.; Parisi, A.; et al.
Highights: PCR assays to detect key mutations of SARS-CoV-2 spike protein are described Discrimination of Variants of Concern (VOCs) and other variants is achieved The assays detected key mutations of 20I/501Y.V1 and 20 J/501Y.V3 in sewage in Italy The method allows rapid and cost-effective detection of VOCs in sewage for WBE The described approach can be used for rapid screening in clinical samples ABSTRACT: New SARS-CoV-2 mutations are constantly emerging, raising concerns of increased transmissibility, virulence or escape from host immune response. We describe a nested RT-PCR assay (~1500 bps) to detect multiple nucleotide changes resulting in key spike protein mutations distinctive of the major known circulating SARS-CoV-2 variants, including the three Variants of Concern (VOCs) 20I/501Y.V1 (United Kingdom), 20H/501Y.V2 (South Africa), and 20 J/501Y.V3 (Brazil), as well as the 20E.EU1 variant (Spain), the CAL.20C recently identified in California, and the mink-associated variant (GR, lineage B.1.1.298). Prior to application to field samples, the discriminatory potential of this PCR assay was explored using GISAID and Nextclade. To extend variant detection to challenging matrices such as sewage, where the amplification of long fragments is problematic, two short nested RT-PCR assays (~300 bps) were also designed, targeting portions of the region spanned by the long nested assay. The three newly-designed assays were then tested on field samples, including 31 clinical samples (7 fully-sequenced swab samples, and 24 uncharacterized ones) and 34 urban wastewater samples, some of which collected in areas where circulation of VOCs had been reported. The long assay successfully amplified 29 of the 31 swabs (93%), allowing the correct identification of variants 20I/501Y.V1 and 20E.EU1 present in the panel of previously characterized samples. The Spanish variant was detected in 14/24 of the uncharacterized samples as well. The sequences obtained using the short assays were consistent with those obtained with the long assay. Mutations characteristic of VOCs (UK and Brazilian variant) and of other variant (Spanish) were detected in sewage samples. To our knowledge, this is the first evidence of the presence of sequences harboring key mutations of 20I/501Y.V1 and 20 J/501Y.V3 in urban wastewaters, highlighting the potential contribution of wastewater surveillance to explore SARS-CoV-2 diversity. The developed nested RT-PCR assays can be used as an initial rapid screening test to select clinical samples containing mutations of interest. This can speed up diagnosis and optimize resources since it allows full genome sequencing to be done only on clinically relevant specimens. The assays can be also employed for a rapid and cost-effective detection of VOCs or other variants in sewage for the purposes of wastewater-based epidemiology. The approach proposed here can be used to better understand SARS-CoV-2 variant diversity, geographic distribution and impact worldwide. Graphycal abstract: Image, graphical abstract